Who Must We Target Now to Minimize Future Cardiovascular Events and Total Mortality?. (September 2015) - Desai, Jay R.; Vazquez-Benitez, Gabriela; Xu, Zhiyuan; Schroeder, Emily B.; Karter, Andrew J.; Steiner, John F.; Nichols, Gregory A.; Reynolds, Kristi; Xu, Stanley; Newton, Katherine; Pathak, Ram D.; Waitzfelder, Beth; et al.
<x xml:space="preserve">Abstract</x> Background— Examining trends in cardiovascular events and mortality in US health systems can guide the design of targeted clinical and public health strategies to reduce cardiovascular events and mortality rates. Methods and Results— We conducted an observational cohort study from 2005 to 2011 among 1.25 million diabetic subjects and 1.25 million nondiabetic subjects from 11 health systems that participate in the Surveillance, Prevention and Management of Diabetes Mellitus (SUPREME-DM) DataLink. Annual rates (per 1000 person-years) of myocardial infarction/acute coronary syndrome (International Classification of Diseases-Ninth Revision, 410.0–410.91, 411.1–411.8), stroke (International Classification of Diseases-Ninth Revision, 430–432.9, 433–434.9), heart failure (International Classification of Diseases-Ninth Revision, 428–428.9), and all-cause mortality were monitored by diabetes mellitus (DM) status, age, sex, race/ethnicity, and a prior cardiovascular history. We observed significant declines in cardiovascular events and mortality rates in subjects with and without DM. However, there was substantial variation by age, sex, race/ethnicity, and prior cardiovascular history. Mortality declined from 44.7 to 27.1 (P<0.0001) for those with DM and cardiovascular disease (CVD), from 11.2 to 10.9 (P=0.03) for those with DM only, and from 18.9 to 13.0 (P<0.0001) for those with CVD only. Yet, in the ≈85% of subjects with neither DM nor CVD, overall mortality (7.0 to 6.8; P=0.10) and stroke rates (1.6–1.6; P=0.77) did not decline and heart failure rates increased (0.9–1.15; P=0.0005). Conclusions— To sustain improvements in myocardial infarction, stroke, heart failure, and mortality, health systems that have successfully focused on care improvement in high-risk adults with DM or CVD must broaden their improvement strategies to target lower risk adults who have not yet developed DM or CVD.